Oil spill detection in Straits of Malacca by using synthetic-aperture radar image - Nurfairunnajiha Ridzuan, 1996-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Project Paper (Sarjana Muda Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2019